Inverted, ’parallel’ accretion of organic material in the cave Setergrotta, Rana, northern Norway: a case study - Dagfinn Moe; Stein-Erik Lauritzen; Rannveig Øvrevik Skoglund (Acta Carsologica, 2016)
The occurrence of an upside-down parallel accretion of organic gyttja, about 10 cm in thickness is reported from the ceiling of an overflow passage in Setergrotta cave, Mo-i-Rana, northern Norway. The deposition process depended on seasonal flooding, was 14C dated back to c. 6500 cal. BC (7645 ± 115 BP). Two pollen diagrams are presented, one from the accretion and one of a nearby minerogenic cave floor deposit. In the accretion sequence, pollen of spruce (Picea abies) was found only in the youngest parts and corresponds to what is known from vegetation historical studies in the region. No significant signals of neither of known vegetation changes caused by climate nor human impact are found in the parallel accretion, contrary to the floor deposit. One of them indicates a marked deforestation dated to about 790 cal. BC in the catchment area for the cave pollen/water supply. Key words: Pollen analysis, 14C date, inverted parallel cave accretion. Obrnjene ‘paralelne’ akrecije organskega materiala v Jami Setergotta, Rana, severna Norveška: študijski primer V članku poročamo o obrnjenih, do 10 cm debelih, paralelnih akrecijah organskega sedimenta (gyttja) v prelivnem rovu jame Settergrotta, Moi-i-Rana, severna Norveška. Odlaganje tega sedimenta je bilo vezano na sezonsko poplavljanje rova. 14C datacije so določili največjo starost 6500 cal. BC (7645 ± 115 BP). Primerjamo tudi pelodna diagrama iz akrecije z diagramom minerogenih sedimentov na jamskih tleh. V zaporedju akrecije smo pelode smreke (Picea abies) našli le v najmlajšem delu, kar ustreza ugotovitvam zgodovinskih študij vegetacije v regiji. V akrecijah nismo našli nobenih pomembnih znakov vegetacijskih sprememb, ki bi jih povzročile klimatske spremembe ali človek. Drugače je v minerogenem sedimentu na jamskih tleh, kjer pelodna analiza kaže na deforestacijo v času 790 cal. BC v zbirnem območju peloda. Ključne besede: Pelodna analiza, 14C datiranje, obrnjene paralelne akrecije.